Образ адресата рекламного текста с точки зрения постулатов речевого общения - Бакланова, Ирина (Studia Rossica Posnaniensia, 2015)
The aim of this paper is to describe the features of advertising texts, which convey implicit information about the character of their target audience. This problem can be solved by analyzing the peculiarities of using Grice’s rules in texts for efficient communication. Information about the expected addressee can be expressed by such means as: (1) the degree of detailed elaboration or compression of information (Maxim of Quantity); (2) the character of argumentation or its absence (Maxim of Quality); (3) the presence or absence of the indicators of semantic relations between the parts of a given text (Maxim of Relation); (4) the character of the style of a given text and/or the language units that are used in it (Maxim of Manner).